Seasonal and Spatial Variations in Fish Assemblage in the Yangtze Estuary and Adjacent Waters and Their Relationship with Environmental Factors - Zhaomin Chen; Qingqiang Ren; Chunlong Liu; Weiwei Xian (Journal of Marine Science and Engineering, 2022)
In this work, we identified the seasonal and spatial variations in fish assemblages and their relation to environmental variables in the Yangtze Estuary and adjacent waters. A total of 61 fish species in 32 families were identified over four seasons; of these, 12 species were dominant and Harpadon nehereus was the most dominant species. Fish varied in abundance, biomass, and species composition in different seasons; both biomass and abundance were highest in autumn and lowest in spring. Fish can be spatially divided into high-salinity assemblages and low-salinity assemblages. The spatial variation in fish assemblages was caused by the selectivity and adaptability of species for the environmental conditions of the estuary and the seasonal variation in fish assemblage structure likely resulted from migrations of dominant taxa associated with fish spawning and foraging behavior as well as the environment. The results of CCA analysis showed that temperature, depth, salinity, dissolved oxygen, and chlorophyll were the major factors affecting the fish assemblage differences throughout the seasons. Of these, temperature drove the seasonal variation in assemblage structure, while salinity significantly affected the spatial distribution of assemblages. This paper revealed the relationship between the seasonal and spatial distribution patterns of the fish assemblage and environmental factors and the results could provide a scientific basis for the management and sustainable utilization of fishery resources in the Yangtze Estuary and adjacent waters.